The parliament and cooperative oversight of the indonesian armed forces: why civil–military relations in Indonesia is stable but still in transition - Ng, Jefferson (2023)
Parliamentary oversight is a cornerstone of democratic control of the armed forces, but its influence on civil–military relations (CMR) remains underexplored. We argue that parliaments in transitioning democracies face unique structural challenges in developing robust oversight of the military compared to advanced democracies. We developed a typology of three distinctive types of parliamentary oversight and proposed that cooperative oversight potentially offers a solution to structural challenges faced by parliaments in transitioning democracies. In our case study of Indonesia, cooperative oversight promoted harmonious working relations between the Parliament and the military/executive, stabilizing CMR. However, cooperative oversight also stalled civil–military reforms, eroded democratic management of the defense sector, and reinforced an unhealthy dependence on the military to self-regulate and the President’s appointment power of the armed forces’ commander. Over the longer term, we believe that the Indonesian Parliament needs to incorporate a mix of oversight strategies and raise its institutional capacity to strengthen oversight of the defence sector.